Update on multidrug-resistant tuberculosis preventive therapy toward the global tuberculosis elimination - Alberto Matteelli; Sofia Lovatti; Benedetta Rossi; Luca Rossi (International Journal of Infectious Diseases)
Multidrug-resistant tuberculosis (MDR-TB), the deadliest form of tuberculosis (TB), has been included in the 2024 World Health Organization (WHO) priority list of antibiotic-resistant bacterial pathogens owing to its severe public health implications. Almost two billion people worldwide are infected with Mycobacterium tuberculosis; however, the share of MDR-M.tuberculosis remains uncertain. Mathematical modeling estimates that MDR-TB affects nearly three in every 1000 people worldwide, highlighting the urgent need to address TB preventive treatment (TPT) for contacts of MDR-TB cases. Before 2018, close monitoring of contacts of people with MDR-TB was recommended rather than TPT. However, considering the ethical and public health concerns associated with leaving infected individuals untreated, the WHO updated its guidelines in 2018, 2020, and 2022. Despite the limited evidence at the time, the WHO suggested considering quinolone-based TPT for selected high-risk cases. To close this gap in evidence, two large-scale prospective randomized controlled trials were conducted: VQUIN (VQUIN MDR Australia New Zealand Clinical Trials Registry number, ACTRN12616000215426) and TB-CHAMP (TB-CHAMP ISRCTN Registry number, ISRCTN92634082). Both trials evaluated the efficacy of levofloxacin (Lfx) compared with a placebo for MDR-TB after household exposure in adults and children. A combined meta-analysis of the two trials showed a 60% reduction in TB incidence in the Lfx group, and the difference was statistically significant. Based on these results, in 2024, the WHO recommended the use of 6 months of daily Lfx as a TPT for contacts exposed to MDR/rifampicin-resistant TB. This regimen is cost-effective, safe, demonstrates good efficacy, and does not interact with HIV therapies. Despite these promising results, pre-extensively drug-resistance (XDR)-TB (MDR-TB with documented resistance to quinolones) remains an emerging concern. Two ongoing trials will address this challenge: the PHOENIx trial (PHOENIx-MDR TB NCT03568383), which will evaluate the efficacy of delamanid compared with isoniazid for preventing M/XDR-TB after household exposure, and the BRANCH-TB trial (NCT0656848), which will assess the efficacy and safety of 1 month of bedaquiline regimen compared with WHO-recommended TPT regimens. Preventing MDR/rifampicin-resistant TB remains a significant challenge for the global elimination of TB. Although the recent WHO recommendation for 6 months of daily Lf is a promising step, expanding the TPT options for pre-XDR TB and addressing drug intolerance are critical. Ongoing and new trials are essential to develop alternative treatment and achieve TB elimination.